Broodstock nutrition in Nile tilapia and its implications on reproductive efficiency - Engdaw, Flipos; Geremew, Akewake (Frontiers in Aquaculture, 2024)
Broodstock nutrition is the most essential constituent of sustainable aquaculture production and its impact on reproductive performance and profitability of commercial aquaculture has been the subject of considerable research. The present paper reviews the literature available on the subject, examining the implication of Nile tilapia broodstock nutrition on parameters such as maturation, fecundity, fertilization, embryo development, larval quality and survival rate.Provision of nutritive diets composed of essential macro and micro-nutrients such as proteins, lipids, carbohydrates, vitamins minerals and functional additives such as prebiotics, enzymes, hormones and probiotics in different proportions is discussed. Special emphasis is given to literature dealing with the effects of dietary protein and lipid on vitellogenesis and ovarian maturation, fecundity, egg hatching rate, larval quality and number of fry survival. The impact of feeding regime on reproductive performance is described.